2015
DOI: 10.1186/s40478-015-0197-z
|View full text |Cite
|
Sign up to set email alerts
|

NHERF1/EBP50 is an organizer of polarity structures and a diagnostic marker in ependymoma

Abstract: NHERF1/EBP50, an adaptor protein required for epithelial morphogenesis, has been implicated in the progression of various human malignancies. NHERF1-deficient mice have intestinal brush border structural defects and we report here that they also have disorganized ependymal cilia with development of non-obstructive hydrocephalus. Examination of mouse and human brain tissues revealed highest NHERF1 expression at the apical plasma membrane of ependymal cells. In ependymal tumors, NHERF1 expression was retained in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 36 publications
4
33
0
Order By: Relevance
“…However, the latter are rare histological findings and in most instances, specific immunohistochemistry is required to confirm diagnosis as in our case. In addition to perivascular cytoplasmic immunoreactivity for GFAP, EMA and EBP50 are useful diagnostic markers that characteristically produce “dot‐like” and “ring‐like” patterns highlighting the intra‐cytoplasmic lumens or microlumens, the pathognomonic ultrastructural feature of ependymomas . These lumens contain microvilli with or without cilia, as was demonstrated on electron microscopy in our case.…”
Section: Discussionsupporting
confidence: 68%
“…However, the latter are rare histological findings and in most instances, specific immunohistochemistry is required to confirm diagnosis as in our case. In addition to perivascular cytoplasmic immunoreactivity for GFAP, EMA and EBP50 are useful diagnostic markers that characteristically produce “dot‐like” and “ring‐like” patterns highlighting the intra‐cytoplasmic lumens or microlumens, the pathognomonic ultrastructural feature of ependymomas . These lumens contain microvilli with or without cilia, as was demonstrated on electron microscopy in our case.…”
Section: Discussionsupporting
confidence: 68%
“…In this approach, NHERF1 IHC may be sent for outside testing to confirm the very rare fibroblastic-like cases from the ED group #1. By using the clinically-validated NHERF1/EBP50 as marker for microlumens [13,16,30], chordoid meningiomas were divided into three ED tumor groups ( Figure 5). Whereas the very rare meningiomas from ED group #1 may be reclassified as WHO grade I, the tumors from the other two groups warrant a higher WHO grade.…”
Section: Discussionmentioning
confidence: 99%
“…By assembling a representative cohort of cases, we have previously shown that this variant is characterized by epithelial differentiation (ED) with microlumen formation [13]. We have also found that immunohistochemistry (IHC) for NHERF1, an adaptor protein that interacts with the ezrin-radixin-moesin (ERM)-NF2 family of proteins to structure microvilli [14,15], specifically highlights microlumens [13,16]. In the current study, we analyzed a 30-patient cohort, performing mutational profiling by next generation sequencing (NGS) and correlating the findings with ED, age, gender, location, and recurrence rate.…”
Section: Introductionmentioning
confidence: 99%
“…NHERF1/EBP50, a protein required for epithelial morphogenesis, appears to be more specific than EMA for labeling ependymomas. 31 In our experience NHERF1 is superior to EMA and extremely helpful in diagnosing difficult cases.…”
Section: Pathologymentioning
confidence: 99%